Effect of Halal Certification and Labelling Process on Halal Supply Chain Performance - Nizamuddin Zainuddin; Adam Mohd Saifudin; Norita Deraman; Norlila Mahidin (International Journal of Supply Chain Management, 2019)
Halal Industry has been growing at a rapid pace due to the growth of the Muslim population worldwide as well as industry internationalization due to tourism and migration. Supply chain management represents a set of interdependent organizations that work closely together to manage the flow of goods or services and information along the value-added chain of products, in order to realize end customer value at the lowest possible costs. Halal Supply Chain performance measures can be developed based on existing measures of the conventional supply chain as long as the primary objective is preserving halal integrity rather than minimizing cost or maximizing profit. The objective of this paper is to see the effect of halal certification and labeling process towards halal supply chain performance using SEM techniques. Halal Certification term as a process of certifying products or services as pronounced by the Shariah Law. halal labeling can be elaborated as marking, tagging or stamping a particular product or service with halal logo or symbol to indicate its halal status. This article focus will be on the survey method only. The instrument development was based on a literature survey. This study focuses on the population of halal-certified food and beverages (F&B) manufacturers as disclose in JAKIM Halal Portal. About 254 questionnaire sets answered by the intended respondents out of 500 being distributed and no data are detected as missing. All questions are completely answered by the respondents. This study has confirmed the effect of Halal Certification and Labelling Process, on Halal Supply Chain performance. Having demonstrated the significance of the hypothesized effect with a substantial total variance explained (i.e. above 75 percent) and sufficient predictive relevance, this study provides strong empirical evidence that a high level of Halal Supply Chain performance can be achieved through the effective implementation of Halal Certification and Labelling Process. Keywords— Halal Industry, Halal Supply Chain performance, Halal certification and labelling, Halal Portal